2010
DOI: 10.3168/jds.2010-3516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interval between induction of ovulation and artificial insemination (AI) and supplemental progesterone for resynchronization on fertility of dairy cows subjected to a 5-d timed AI program

Abstract: Objectives were to investigate 2 intervals from induction of ovulation to artificial insemination (AI) and the effect of supplemental progesterone for resynchronization on fertility of lactating dairy cows subjected to a 5-d timed AI program. In experiment 1, 1,227 Holstein cows had their estrous cycles presynchronized with 2 injections of PGF(2α) at 46 and 60 d in milk (DIM). The timed AI protocols were initiated with GnRH at 72 DIM, followed by 2 injections of PGF(2α) at 77 and 78 DIM and a second injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 30 publications
9
76
1
7
Order By: Relevance
“…given 24 hours after CIDR removal in 5d-GnRH-based protocols has provided controversial results. Two doses of PGF in the 5d TAI protocols improved luteolysis and pregnancy rates in dairy cows (Bisinotto et al, 2010;Santos et al, 2010), and heifers (Lima et al, 2013). However, Garcia-Ispierto & Lópes-Gatius (2014) did not observe similar beneficial effects on dairy cows.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…given 24 hours after CIDR removal in 5d-GnRH-based protocols has provided controversial results. Two doses of PGF in the 5d TAI protocols improved luteolysis and pregnancy rates in dairy cows (Bisinotto et al, 2010;Santos et al, 2010), and heifers (Lima et al, 2013). However, Garcia-Ispierto & Lópes-Gatius (2014) did not observe similar beneficial effects on dairy cows.…”
Section: Resultsmentioning
confidence: 94%
“…However, based on the results of a previous study (Martinez et al, 2005) and on the foundational nature of the current work, we were not encouraged to risk using TAI in a large number of cows without treating them with an ovulation inducer. Considering that 55 to 65% of the cows are still not pregnant after the first postpartum AI (Bisinotto et al, 2010), the substitution of EB by PGF as the ovulation inducer in a TAI protocol provided satisfactory fertility in dairy cows (~40%). The acceptable pregnancy rates, obtained in both EB and PG groups (Table 1), is an evidence that ovulation probably occurred in a synchronous manner in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been clearly shown in numerous studies using timed AI programs (Souza et al, 2007;Brusveen et al, 2008;Bisinotto et al, 2010b;Giordano et al, 2012b and. In addition, studies on cows that receive AI after detection of estrus, have generally reported that minor elevations in P4 near AI are also detrimental to fertility (De Silva et al, 1981;Waldmann et al, 2001;Ghanem et al, 2006), although some studies did not obtain this result (Erb et al, 1976;Plym Forshell et al, 1991).…”
Section: Pregnancy Loss In Dairy Cowsmentioning
confidence: 96%